Integrating water resources into computable general equilibrium models: A survey - Roberto Ponce; Francesco Bosello; Carlo Giupponi (Fondazione Eni Enrico Mattei (FEEM), 2012)
Water resources are facing several stresses in terms of quantity and quality. These pressures are closely related to the human interventions in fields like: agriculture, land-use/land use change, construction/management of reservoirs, pollutant emissions, and water /wastewater treatment, among others. Considering the critical role that water plays for agricultural production, any shock in water availability will have great implications for agricultural production, and through agricultural markets these impacts will reach the whole economy with economy-wide consequences. The aim of this report is to present a literature review about the state of the art methodology regarding the study of water issues using the CGE approach at global and national scale. The analysis of the different studies confirms the economy wide consequences of changes in water allocation, irrigation policies, and climate change, among others water related issues.
Keywords: C68; Q18; Q25; Q54; 330; Computable General Equilibrium Models; Water; Irrigation; Agricultural Policy; Water Allocation